Chionanthus monteazulensis (Oleaceae), a new species from the campo rupestre of Espinhaço Range, Brazil - Alvarenga Zavatin, Danilo; Baptista Pereira Almeida, Roberto; Ramos, Renato; Lombardi, Julio Antonio (Phytotaxa, 2023)
The new species Chionanthus monteazulensis, from Minas Gerais State, Brazil, is here described and illustrated. It differs from somewhat similar C. fluminensis by the inflorescence size, two stamens (vs. four), the smaller and orbicular or wide-elliptic blades, and the smaller petals and fruits.